Telaah Wacana Imperialisme Budaya Tokusatsu Jepang Melalui Iklan Marjan Versi Wayang Golek - Halla Puspita Yuri; Hartanto Jahja; Rewindinar Rewindinar; Yuri Alfrin Aladdin; Rustono Farady Marta (Fakultas Ilmu Komunikasi UKWMS, 2020)
Technological progress in the field of robotics is something that is idolized in homeland. Robotics often appears along with the tendency of the Japan which is popular with futuristic technology. Indonesia is affected by Japan's tokusatsu shows because we ourselves are still lagging behind in the fields of technology and culture. The era of Japanese colonialism towards Indonesia over the past 3.5 years seemed to reincarnate into cultural imperialism, one of which can be listened to through the Marjan syrup ads version of